MODERN FEATURES OF APPLIED PHYSICS TRAINING IN THE PREPARATION OF FUTURE PHYSICS TEACHERS - Usembaeva, И.Б; Berdi, Д.К; Sarybayeva, Ә.Х; Baymakhanovа, А.С (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article analyzes scientific research on the modern possibilities of teaching the course. Methods, tools, the existing potential for training future teachers of physics, the use of the applied orientation of physics training, the implementation of the applied orientation of teaching in domestic and foreign universities were formulated and defined. In the implementation of the applied orientation of teaching physics, the criteria for the selection of educational material of an applied nature are determined. In addition, various ways of the necessity of applying physical knowledge in practice, the importance of using the process of solving problems to form the applied focus of physics training, are examined. The article analyzes qualitative problems of an applied nature, including the purpose and methods of solving such problems, methods of applying students' theoretical knowledge in practical classes.